ANALISIS KINERJA KEUANGAN PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER SEBELUM DAN SAAT COVID-19 - Nabila Savitri (2022)
This study was conducted to find out whether there are differences in the financial performance of the Primary Consumer Goods Sector Companies between before and during the Covid-19 outbreak. This study uses a probability sampling technique using the Slovin formula, and the number of samples obtained is 72 companies. The period in this study is one year before and one year during the occurrence of Covid-19. Data processing using SPSS 28 with the Wilcoxon Signed Rank Test analysis technique. The results in the study state that the profitability and activity variables are different, as well as for the liquidity and solvency variables there are no differences before and during Covid-19.